Effects of motor skill level and speed on movement variability during running. (11th October 2021) - Wang, Wei; Qu, Feng; Li, Shangxiao; Wang, Liduan
Abstract: Variability in movement is an informative biological feature. This study aimed to examine the effects of motor skill level and running speed on movement variability. Twenty-nine male college students (fourteen athletes and fifteen non-athletes) participated in this study. All participants performed three motor tasks: 3 m/s running, 5 m/s running, and sprint running. Lower-limb kinematic data were acquired using a 16-camera infrared motion capture system. Lower-limb coordination during the stance phase was quantified using a continuous relative phase (CRP) method for interlimb (hip-hip, knee-knee, ankle-ankle) and intralimb (hip-knee, knee-ankle). The variabilities of stride length, stride cadence, joint angles, intralimb CRP, and interlimb CRP were calculated as standard deviations of each measurement. The results revealed that there were significant interaction effects between motor skill level and speed on movement variability for stride length (p = 0.047), ankle angle during propulsive phase (p = 0.001), knee-ankle CRP during propulsive phase (p = 0.007) and knee-knee CRP during propulsive phase (p = 0.009). Athletes showed greater angle variability, coordination variability and lower stride length variability during sprinting (all p < 0.05). In contrast, no between groups variability difference was observed when jogging at fixed lower speeds (all p > 0.05). Movement variability was greater for sprinting compared to jogging. Skill level was found to differentially affect the role of coordination variability in sprint performance. For athletes, hip-knee deviation phase and hip-hip deviation phase during braking phase were negatively correlated with sprinting speed (r = -0.563 and −0.642, respectively; both p < 0.05). For non-athletes, hip-knee deviation phase was positively correlated with sprinting speed (r = 0.581, p = 0.023). In conclusion, stride length become more stable, joint angle and coordination become more variable with long-term training. Results of this study also suggest that the relationship between coordination variability and performance is complicated and may depend on motor skill level. More longitudinal studies are needed to definitively determine the relationship between movement variability and performance.